2013
DOI: 10.1016/s0140-6736(13)60554-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of TCF12, encoding a basic-helix-loop-helix partner of TWIST1, are a frequent cause of coronal craniosynostosis

Abstract: Craniosynostosis, the premature fusion of the cranial sutures, is a heterogeneous disorder with a prevalence of ~1 in 2, 200 (refs. 1,2). A specific genetic etiology can be identified in ~21% of cases 3 , including mutations of TWIST1, which encodes a class II basic helix-loop-helix (bHLH) transcription factor, and causes Saethre-Chotzen syndrome, typically associated with coronal URLs. ANNOVAR, http://www.openbioinformatics.org/annovar; GBrowse2, http://gmod.org/wiki/GBrowse; MRC-Holland, www.mrc-holland.com/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 17 publications
7
79
0
Order By: Relevance
“…In the present study, we demonstrated that silencing Tcf12 significantly increased the osteogenic potential of BMSCs in vitro, thus indicating an inhibitory osteogenic activity of this transcription factor in BMSCs. Of note, these findings are consistent with previous reports indicating that mutation of Tcf12 leads to craniosynostosis .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, we demonstrated that silencing Tcf12 significantly increased the osteogenic potential of BMSCs in vitro, thus indicating an inhibitory osteogenic activity of this transcription factor in BMSCs. Of note, these findings are consistent with previous reports indicating that mutation of Tcf12 leads to craniosynostosis .…”
Section: Discussionsupporting
confidence: 80%
“…Basic helix‐loop‐helix (bHLH) genes constitute a large family of transcription factors (TFs) found in eukaryotic organisms, which orchestrates cell‐fate specification, commitment and differentiation in multiple cell lineages during development . Tcf12 is a transcription factor member of the bHLH family that regulates a variety of biological processes including immune response, metastasis of colorectal cancer, cognitive function and craniosynostosis . Tcf12 (also named HEB) has two gene products, HEBa and HEBb.…”
Section: Introductionmentioning
confidence: 99%
“…The participation of TF in tumorigenesis is widely studied (Darnell, 2002; Harris, 2002; Zheng and Blobel, 2011; Gupta et al, 2019), including the most famous TF p53 (TP53 gene) (Harris, 1993; Staib et al, 2003; Muller and Vousden, 2013). However, when the three gene lists are compared (TF, cancer driver, CRS), only one gene, TCF12 (Lee et al, 2012; Sharma et al, 2013), appears in all lists.…”
Section: Discussionmentioning
confidence: 99%
“…Though craniosynostosis is a feature of many syndromes, single sutural synostosis is most commonly an isolated, nonsyndromic finding [2]. Some of these nonsyndromic patients may have an underlying genetic etiology for their phenotype [3]. There may be overlap in the appearance of multisutural synsotosis among different syndromes, though characteristic associated hand dysmorphology may help to distinguish one from the other.…”
Section: Introductionmentioning
confidence: 99%